Revealing turbulent dark matter via merging of self-gravitating condensates - Sivakumar, Anirudh; Mishra, Pankaj Kumar; Hujeirat, Ahmad; Muruganandam, Paulsamy (Physical review, 2025)
Self-gravitating condensates have been proposed as potential candidates for modeling dark matter. In this paper, we numerically investigate the dynamics of dark matter utilizing the merging of self-gravitating condensates. We have used the Gross-Pitaevskii-Poisson model and identified distinct turbulent regimes based on the merging speed of the condensate. As a result of collision, we notice the appearance of various dark soliton-mediated instabilities that finally lead to the turbulent state characterized by Kolmogorov-like turbulence scaling 𝜖𝑖kin ∼𝑘−5/3 in the infrared and 𝜖𝑖kin ∼𝑘−3 in the ultraviolet regions. The compressible spectrum suggests weak-wave turbulence. The turbulent fluctuations in the condensate cease as the vortices formed via soliton decay are expelled to the condensate’s periphery, manifested in the transferring of kinetic energy from incompressible and compressible flows to the quantum pressure energy. We also establish the significant role played by the self-gravitating trap in determining the distribution of compressible kinetic energy and the resulting density waves, which differ markedly from those observed in atomic condensates under harmonic confinement. Our study may offer valuable insights into the merging of binary stars and open new avenues for understanding the structure and dynamics of the dark matter through self-gravitating condensate.